2016
DOI: 10.1681/asn.2016070780
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Balance and Prescription in ESRD

Abstract: The optimal approach to managing acid-base balance is less well defined for patients receiving hemodialysis than for those receiving peritoneal dialysis. Interventional studies in hemodialysis have been limited and inconsistent in their findings, whereas more compelling data are available from interventional studies in peritoneal dialysis. Both high and low serum bicarbonate levels associate with an increased risk of mortality in patients receiving hemodialysis, but high values are a marker for poor nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 100 publications
4
35
0
1
Order By: Relevance
“…Mechanistically, high-bicarbonate dialysate/prescription has been shown to have effects on the QT interval [12,13], hemodynamics [14][15][16], levels of serum potassium [17], and ionized calcium [18], which may increase the risk for ventricular arrhythmia [19][20][21]. Studies have linked changes in ionized calcium to high bicarbonate dialysate prescription [18,22], but we only had data on total calcium, and hence could not study the effects on ionized calcium, while other studies have found results similar to ours [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, high-bicarbonate dialysate/prescription has been shown to have effects on the QT interval [12,13], hemodynamics [14][15][16], levels of serum potassium [17], and ionized calcium [18], which may increase the risk for ventricular arrhythmia [19][20][21]. Studies have linked changes in ionized calcium to high bicarbonate dialysate prescription [18,22], but we only had data on total calcium, and hence could not study the effects on ionized calcium, while other studies have found results similar to ours [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing controversy regarding the optimal composition of dialysate, especially with regard to sodium, potassium, and bicarbonate . Differences in dialysate composition may influence both clinical and patient related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There is ongoing controversy regarding the optimal composition of dialysate, especially with regard to sodium, 6-9 potassium, [10][11][12] and bicarbonate. [13][14][15] Differences in dialysate composition may influence both clinical and patient related outcomes. Higher dialysate sodium concentrations have been associated with higher postdialysis blood pressure measurements and larger interdialytic weight gains (IDWG).…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is the differential effect of OL-HDF versus HD on PaCO 2 levels. It is understood that patients' PaCO 2 will rise during dialysis treatment due to the production of CO 2 from dialysate bicarbonate [29,30], and that rapid elevation of PaCO 2 can trigger chemoreceptors and cause respiratory disturbance [29]. Dysfunctional chemoreceptor responsiveness is believed to be the major cause of CSA in patients with kidney disease [31] and patients with ESKD are known to have increased chemoreceptor sensitivity [32].…”
Section: Discussionmentioning
confidence: 99%